The Drosophila odz/ten-m gene encodes a type I, multiply cleaved heterodimeric transmembrane protein. - Dgany, O.; Wides, R. (The Biochemical Journal, 2002)
The product of the Drosophila melanogaster odd Oz (odz)/Tenascin-major (ten-m) pair-rule gene consists of eight epidermal growth factor (EGF)-like repeats followed by a novel 1800 amino acid polypeptide stretch unique to proteins of the Odz/Ten-m family. The structure and membrane orientation of this large enigmatic protein was characterized by raising and employing antibodies directed against discrete Odz polypeptide regions. Protein-modifying reagents impermeable to the plasma membrane were used in concert with the battery of antibodies to demonstrate that Odz is a type I transmembrane protein with the vast C-terminal portion in the intracellular space, and with the EGF repeats deployed extracellularly. The polypeptide was shown to undergo multiple cleavages at discrete intracellular and extracellular sites, and its extreme C-terminus was shown to undergo either processing at a very large number of sites or programmed degradation. The polypeptide is presented at the cell surface with additional post-translational modifications, and as two subunits of previously cleaved Odz joined by cysteine disulphide bridges maintaining their association. The model derived for the Odz protein is discussed in light of other models proposed for proteins of the Odz/Ten-m family, and in terms of functional implications.